Silhouette + attraction: A simple and effective method for text clustering†. (14th August 2015) - ERRECALDE, MARCELO L.; CAGNINA, LETICIA C.; ROSSO, PAOLO
Abstract: This article presents silhouette–attraction ( Sil–Att ), a simple and effective method for text clustering, which is based on two main concepts: the silhouette coefficient and the idea of attraction . The combination of both principles allows us to obtain a general technique that can be used either as a boosting method, which improves results of other clustering algorithms, or as an independent clustering algorithm. The experimental work shows that Sil–Att is able to obtain high-quality results on text corpora with very different characteristics. Furthermore, its stable performance on all the considered corpora is indicative that it is a very robust method. This is a very interesting positive aspect of Sil–Att with respect to the other algorithms used in the experiments, whose performances heavily depend on specific characteristics of the corpora being considered.